Al-Ittijāhāt al-Munḥarifah fī at-Tafsīr li-Ba‘ḍ Aṣḥāb al-Maẓāhib an-Naḥwīyah wa-Ba‘ḍ min Yajhalūn Qawā‘id al-Lughah al-‘Arabīyah fī Naẓar Muḥammad Ḥusaen adh-Dhahabī - Misbakhudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
One of the most precious achievement in qur’anic studies was the book of Al-Ittijâhât alMunharifah fî al-Tafsîr: Dawâfi’uha wa Daf’uha written by A great Islamic scholar, Muhammad Husein al-Dzahabî. He was succeeded in discussing several issues of corruptions of the exegesis of the holy Qur’an. This article is aimed to explain and to describe his analysis toward several corrupted linguist interpretations in their originations and such corrupted linguistic interpretations of the holy Qur’an which are ignoring Arabic structures and grammers.